An Unusual Venous Plexus on Psoas Major Muscle Connecting the Inferior Mesenteric and Testicular Veins - Satheesha Nayak B.,; Bincy MG.,; Snigdha M.,; Srinivasa Rao S.,; Surekha DS., (Department of Surgery, UKM Medical Centre, 2015)
Knowledge of communication between parietal abdominal veins, testicular vein and mesenteric veins is important for Surgeons, Urologists and Radiologists. These communications can result in varicocele or hemorrhoids and may lead to low success rate in hemorrhoid and varicocele surgeries. During routine dissection classes, we observed an unusual large venous plexus on the left psoas major muscle. The venous plexus was unilateral and was formed by many anastomotic venous channels on the psoas fascia and communicated with the left testicular and inferior mesenteric veins. The testicular and inferior mesenteric veins were significantly enlarged below the level of communication with the venous plexus.